1970
DOI: 10.3126/nepjoph.v4i1.5844
|View full text |Cite
|
Sign up to set email alerts
|

Demographics and awareness of diabetic retinopathy among diabetic patients attending the vitreo-retinal service at a tertiary eye care center in Nepal

Abstract: A lack of awareness of DR coupled with a high proportion of cases already at a sight-threatening stage of retinopathy at their first presentation reflects the need for improved awareness programs to reduce the burden of blindness from DR in Nepal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
58
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 7 publications
9
58
3
Order By: Relevance
“…This was low when compared to studies done in Bagalkot (76.6%) [2] and Malaysia (91.2%) [12] wherein most of them felt the need for eye checkup when his/her diabetes was uncontrolled and only 23.3% felt the need for eye checkup even with controlled diabetes as per study done in Bagalkot, [2] whereas 67.2% as per Malaysia study. [12] More than half of the patients were aware about various complications arising from uncontrolled diabetes mellitus, and similar findings were seen in the study done in Bagalkot [2] and the most common source of knowledge about complications was medical personnel similar to studies done in Bagalkot, [2] Nepal, [10] and Jordan. [11] In the present study, when patients were asked about frequency of regular eye checkup, 70.7% felt that they need to go for it only when vision is affected which is in contrast to the findings of a study done in Bagalkot [2] and Malaysia [12] where it was 38% and 21.9%, respectively.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This was low when compared to studies done in Bagalkot (76.6%) [2] and Malaysia (91.2%) [12] wherein most of them felt the need for eye checkup when his/her diabetes was uncontrolled and only 23.3% felt the need for eye checkup even with controlled diabetes as per study done in Bagalkot, [2] whereas 67.2% as per Malaysia study. [12] More than half of the patients were aware about various complications arising from uncontrolled diabetes mellitus, and similar findings were seen in the study done in Bagalkot [2] and the most common source of knowledge about complications was medical personnel similar to studies done in Bagalkot, [2] Nepal, [10] and Jordan. [11] In the present study, when patients were asked about frequency of regular eye checkup, 70.7% felt that they need to go for it only when vision is affected which is in contrast to the findings of a study done in Bagalkot [2] and Malaysia [12] where it was 38% and 21.9%, respectively.…”
Section: Discussionsupporting
confidence: 70%
“…[9] This awareness was low as compared to studies done in Vellore (71.9%) [1] , Nepal (63.3%), [10] and Jordan (98.3%). [11] Majority of the patients 83.3% believed that individuals with controlled diabetes will have no eye problem which is higher as compared to the findings done in Bagalkot (68%) [2] and Malaysia (51.1%).…”
Section: Discussionmentioning
confidence: 97%
“…Despite higher awareness of diabetic retinopathy that could lead to blindness among diabetic patients in Kano Nigeria, only 15.7% of then ever had an eye check up (Mohammed & Waziri, 2009). It was also demonstrated that some of the diabetes patients had no or lower knowledge with regards to regular eye check up and the frequencies of follow up (Ovenseri-Ogbomo et al, 2013;Shetgar et al, 2015;Thapa et al, 2012). They did not know that eye examination is essential to those who own diabetic.…”
Section: Introductionmentioning
confidence: 99%
“…Majority of the studies was done among diabetes mellitus patients in hospital except for study in rural India which was conducted among public population (Rani et al, 2008). In Nepal, during the awareness investigation among diabetes patients, it was found that 78% had retinopathies, 16.7% had proliferative stage and 40% had significant diabetic macula edema (Thapa et al, 2012). This showed that lack of awareness of diabetic retinopathy; the patients could have low knowledge of the disease and missed the symptoms or signs that occurred due to ocular complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation